9. The Concept of Nature and Its Applications in the Legal, Musical and Educational Fields - Marisi Flavia (Sciendo, 2016)
The concept of nature changed over time, modifying the relationship between nature and man: in some cultures man and nature are considered as deeply connected, in others definitely separated. The leading ideas about nature are reflected in work pertaining to the legal, musical and educational fields. This study provides insights into these issues, trying to highlight specific analogies which connect the concept of nature and its application in the cited fields.